Evaluation of acute toxicity, genotoxicity and inhibitory effect on acute inflammation of an ethanol extract of Morus alba L. (Moraceae) in mice. (24th December 2016) - Oliveira, Alisson Macário de; Nascimento, Matheus Ferreira do; Ferreira, Magda Rhayanny Assunção; Moura, Danielle Feijó de; Souza, Talita Giselly dos Santos; Silva, Gabriela Cavalcante da; Ramos, Eduardo Henrique da Silva; Paiva, Patrícia Maria Guedes; Medeiros, Paloma Lys de; Silva, Teresinha Gonçalves da; Soares, Luiz Alberto Lira; Chagas, Cristiano Aparecido; et al.
Abstract: Ethnopharmacological relevance: Morus alba L. (white mulberry) is used in traditional medicine worldwide, including Brazil. The leaves of this plant are used to treat inflammatory disorders. Universal interest in this plant necessitates studies on the toxicological safety and scientific substantiation of the medicinal properties of M. alba . In previous work, we investigated the acute toxicity of orally administered M. alba ethanol extract in mice. Aim of the study: This work was designed to investigate the ethanol extract obtained from M. alba leaves for acute toxicity when intraperitoneally administered, in vivo genotoxicity, and potential to reduce acute inflammation. In order to further investigate the constituents of the extract, we also obtained the high-performance liquid chromatography (HPLC) fingerprint of the extract. Materials and methods: Phytochemical analysis by thin layer chromatography (TLC) was performed and the results were used to obtain the HPLC fingerprint. Acute toxicity of 300 and 2000 mg/kg b.w. i.p. doses administered to mice for 14 days was evaluated. Genotoxicity was evaluated by counting the number of micronucleated polychromatic erythrocytes in the blood of mice that either received or did not receive the extract at 75, 150 and 300 mg/kg b.w. per os . The anti-inflammatory effect of the same doses administered per os was investigated using the carrageenan air pouch model. Results: The TLC analysis of the extract revealed the presence of a remarkable amount of flavonoids and cinnamic acids. The HPLC fingerprint showed the presence of one major peak corresponding to chlorogenic acid and two smaller peaks corresponding to flavonoids. In the toxicity assays, there were no deaths or deviations in behavior of treated mice as compared to the control at any dose. However, biochemical, hematological, and histological analyses showed that intraperitoneal injection caused several forms of damage to the mice, which were not observed in case of oral administration, studied in our previous work. Oral administration of the extract did not result in genotoxicity and considerably reduced (58.6–65.6% inhibition) leukocyte migration in all doses evaluated, in comparison with the negative control. Conclusions: The ethanol extract from M. alba leaves administered intraperitoneally possesses a greater degree of toxicity in mice when compared to per os administration. The extract was not genotoxic when ingested by mice and exhibited a highly inhibitory effect against acute inflammation, which is probably linked to the presence of chlorogenic acid and flavonoids in the composition. This work contributes to the determination of safety of the medicinal use of M. alba leaves. Graphical abstract: